PENENTUAN KAPASITAS PENGAMBILAN PT.PSP BERDASARKAN ANALISA NERACA AIR SUB DAS CEMPAGA DAS MENTAYA WS MENTAYA KATINGAN - Kiki Frida Sulistyani; Danang Bimo Irianto (Universitas Islam Balitar Blitar, 2023)
PT Pelaran Sawit Perkasa (PSP) is located in Bukit Batu Village, Cempaga Hulu District, East Kotawaringin Regency, Central Kalimantan. PT PSP needs water for palm oil industry activities and raw water in employee settlements. PT PSP's intake is in the Cempaga watershed. The Cempaga Watershed has an area of 983.83 square kilometers, with the dominant land use of plantations amounting to 76.2% of the total watershed area. From the results of the FJ Mock analysis, the average discharge data for 15 days is between 30.12 m3/second to 108.36 m3/second. The maintenance discharge was calculated using the Flow Duration Curve method and obtained discharge rates ranging from 4.38 m3/second in the driest season to 56.96 m3/second in the rainy season. Intake Cempaga is planned to serve WTP with a production capacity of 16.7 liters/second or 1 m3/minute with an operational pattern of taking water for 20 hours/day and a collection period of 26 days per month. The results of the water balance at the Cempaga intake are surplus, with values between 0.42 m3/second to 26.21 m3/second.